Mild Local Hyperthermia Enhances the Transdermal Permeation of Ketotifen - Pandey, V.P.; Balaji, Anna; Shivakumar, H.N.; Srinivasan, N. (Asian Journal of Chemistry, 2010)
The permeation of ketotifen fumarate across rat skin was studied at 37 and 40 °C. The flux was enhanced at 40 °C by 18 fold over 37 °C. Diffusion studies across dialysis membrane and stripped skin at two temperatures revealed that the primary mechanism of enhancement at mild hyperthermia conditions is most likely due to the alteration of physicochemical nature of stratum corneum lipids and additionally due to the increased kinesis of molecules. The results show how an increase in temperature by a few degrees above physiological temperature increases the permeation of hydrophilic drugs.